White sponge nevus: A case report of a rare keratinopathy and its novel treatment approach (Indian Journal of Case Reports, 2020)
White sponge nevus (WSN) is a hereditary mucocutaneous leukokeratosis due to an altered expression of CK 4 and CK 13 genes, thereby causing a defect in keratinization. We report the case of WSN in a 27-year-old who presented with a complaint of white, painless patches in both the cheek mucosa since childhood. The patient was examined and the biopsy was done. Based on the clinical findings, inheritance pattern, and histopathological features, a diagnosis of WSN was made. The patient responded well to our novel treatment approach with amoxicillin suspension (250 mg/5 ml). Regarding the treatment of WSN, no definite pharmacological therapy is available till date. We report this case to emphasize that amoxicillin suspension topical therapy may be used as a novel treatment measure with its unique advantages.